Conflitos sócio-ambientais entre os tembé do alto rio Guamá - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2005)
This project focuses on the study of the socio-environmental issue in the Alto Rio Guamá Indigenous Reserve (PA), considering the areas occupied by the Tembé of Guamá. The general objective is to study the conflicts generated by timber exploitation in the area, with the specific aim of getting to know the actors involved, analyzing the possible conflicts derived from it, and what action the Tembé and responsible bodies (FUNAI, IBAMA and others) have taken to prevent such exploitation in the reserve. This study is in addition to others on this group, such as those by Alonso (1996) and Sales (2000). The study is based on field research, using techniques such as direct observation and informal interviews carried out in the villages of São Pedro, Tawari, Itaputyre, and Frasqueira. Bibliographic and documental research - in particular newspaper clippings found in the libraries of CIMI and FUNAI - have also been used. The exploitation of timber and other natural resources in the area has been going on for decades. According to Alonso (1996), the 1960s saw the concentration of land in the hands of loggers and ranchers in the Amazon, the effects of which also affected the reserve in question. Conflicts related to this illegal activity have generated discord within the Tembé society, not being, according to some indigenous people interviewed, responsible for splits in the group. The intense exploitation of resources - essential for their survival - and the devastation of the reserve have generated sociocultural, economic (cattle raising and beekeeping), and political changes among the Tembé of the upper Guamá River
Socio-environmental conflicts among the Tembé of the upper Guamá River
Keywords: Tembé; Conflitos ambientais; CNPQ::CIENCIAS HUMANAS